Contribution of Village Government and its Impact on Maternal and Child Health in Medan Estate Village, Percut Sei Tua District - Simbolon, Nur Anisa; Hilda Samura, Laras; Uli Sembiring, Vanessa; Harmoni Sembiring, Dian Wahyu; Ivanna, Julia (JUPE : Jurnal Pendidikan Mandala, 2024)
This research intends to see how the village government contributes and also its impact on maternal and child health in Medan Estate Village, Percut Sei Tua subdistrict. The research method used is a qualitative approach. To collect data, this research uses data collection techniques through observation, interviews and documentation. The success of improving the quality of public services reflects good government performance. The research results obtained were in implementing a program to improve public services, the Medan Estate Village government implemented several programs such as the maternal and child health program through Integrated Healthcare Center. The program includes ID cards (nuts, eggs, bananas) which are given every 3 months and providing spiritual understanding to the prospective bride and groom is also carried out.